Identification of interspecific hybrid between Jatropha curcas × J. integerrima using morphological and molecular markers - DARMAWAN SAPTADI; NUR ASBANI; BAMBANG HELIYANTO; ASEP SETIAWAN; SUDARSONO (Society for Indonesian Biodiversity, 2020)
Abstract. Saptadi D, Asbani N, Heliyanto B, Setiawan A, Sudarsono. 2020. Identification of interspecific hybrid between Jatropha curcas x J. integerrima using morphological and molecular markers. Biodiversitas 21: 814-823. Eight F1 progenies derived from Jatropha curcas × J. integerrima hybridizations were evaluated for their morphological characters and using RAPD, ISSR and SSR markers. Morphological variations among the hybrids were limited and they were intermediate between the Jatropha parents. The eight F1 progenies derived from J. curcas × J. integerrima hybridizations were most probably the interspecific F1 hybrids. The confirmed identity of the progenies as interspecific hybrids between J. curcas × J. integerrima was based on the presence of several phenotypic characters from both parents in the F1 progenies and by similarity of the molecular marker banding patterns among the parents and the F1 progenies. Among the evaluated molecular markers, the ISSR primers and the majority of either RAPD and SSR primers were not able to generate marker for confirming the identity of F1 progenies as interspecific hybrids between J. curcas × J. integerrima. However, the RAPD primer OPC 10 and the SSR primers AF469003, EU099522 and EU586348 were able to generate polymorphic markers in the Jatropha parents and their F1 progenies. Therefore, these four primers were able to generate usable markers for confirming the identity of F1 progenies as interspecific hybrids between J. curcas × J. integerrima. The evaluated interspecific F1 progenies are potentially useful to increase genetic diversity of J. curcas and support its breeding program.